How social inequalities impact the course of treatment and care for patients with type 2 diabetes mellitus: study protocol for a qualitative cross-sectional study from the patient's perspective. Issue 7 (10th July 2015) - Baumann, Amelie; Schröder, Sara L; Fink, Astrid
Abstract : Introduction: Studies from various scientific disciplines have demonstrated that socioeconomic inequalities in type 2 diabetes mellitus negatively affect groups with a low socioeconomic status. Furthermore, socioeconomic inequalities also exist in terms of access to, and utilisation and perceived quality of, diabetological care. The aim of this qualitative study, which focuses on the patient's perspective, is to provide insights into the ways socioeconomic inequalities impact the course of treatment and care of patients with type 2 diabetes mellitus. The study aims to develop an understanding of how socioeconomic inequalities in care arise. Methods and analysis: A cross-sectional qualitative study will be conducted using a sample of about 20 patients with type 2 diabetes mellitus aged 18 and older. Patients will be recruited successively from the University Hospital in Halle/Saale, Germany, a general practitioner's office, and in a specialised diabetological practice. The patients will be interviewed personally once, using semistructured qualitative interviews. All interviews will be recorded, transcribed, and analysed based on Grounded Theory. Ethics and dissemination: All interviewees will receive comprehensive written information about the study and sign a declaration of consent prior to the interview. The study will comply rigorously with data protection legislation. The research team has obtained the approval of the Ethical Review Committee at the MLU Halle-Wittenberg, Germany. The results of the study will be published in high-quality, peer-reviewed international journals, presented at several congresses and used for developing follow-up research projects. Trial registration number: This study has been registered with the German Clinical Trials Register and assigned DRKS00007847.